ANTHROPOMORPHIC AI AND ADVERTISING APPEAL INCREASING EXPLORATION OF PURCHASE INTENTION IN MEDIATION CONSUMER PREFERENCE - Firmansyah, Hary; Yuni, Nurna (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Making a product as top of mind in consumers' minds was a long process that involves various things, including currently many companies were using artificial intelligence programs to support the process of introducing products to consumers. This research involved 172 consumers whom stay in Tasikmalaya City and used quantitative data with the PLS-SEM analysis tool as the data analysis tool used. The research results reveal that humanistic artificial intelligence has no effect on increasing exploration of purchasing interest which was mediated by consumer preferences. Furthermore, the advertising approach has an effect on increasing exploration of purchasing interest which was mediated by consumer preferences. Together, humanistic artificial intelligence and an advertising approach have an effect on increasing the exploration of purchasing interests mediated by consumer preferences.